(untitled) (Global Journal of Medical Research, 2018)
A secondary middle turbinate is considered a rare anatomical variation of the middle turbinate. Here, we present a case of young lady who presented to our clinic with signs and symptoms of chronic rhinosinusitis and headach. On nasal endoscopy and CT sinuses, she was found to have a left secondary middle turbinate, obstructing the left osteomeatal complex. Functional endoscopic sinus surgery was performed to the patient with excellent postoperative results and no evidence of recurrence of her symptoms during a three month follow up.